(10x-2)=55+63

Simple and best practice solution for (10x-2)=55+63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (10x-2)=55+63 equation:


Simplifying
(10x + -2) = 55 + 63

Reorder the terms:
(-2 + 10x) = 55 + 63

Remove parenthesis around (-2 + 10x)
-2 + 10x = 55 + 63

Combine like terms: 55 + 63 = 118
-2 + 10x = 118

Solving
-2 + 10x = 118

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 10x = 118 + 2

Combine like terms: -2 + 2 = 0
0 + 10x = 118 + 2
10x = 118 + 2

Combine like terms: 118 + 2 = 120
10x = 120

Divide each side by '10'.
x = 12

Simplifying
x = 12

See similar equations:

| (3x+15)=(4x-10) | | -3/10y=-6 | | 6w+5=9w+2 | | (2x+5)=33 | | 6x+5y+2x-2y= | | .16(y-6)+.02y=.08y-.7 | | 3w+4=2w+11 | | 0.6y+6.5=0.5(9+y) | | 6p=91 | | 6x+5y+2x= | | 28-2x=34 | | (6x)+(4x-3)=46 | | -4.5x+1.1=-16.9 | | 4(2x-8)-7=4(x-4)+5 | | .7x+4.2=.6x+1.4 | | 7x+6x(4)=-93 | | 14x-(6x-3)=59 | | 2(4z+1)-7=59 | | 6[2-(3+4x)]-2x=-8+2(1-13x) | | (2x-2)+(5x-7)= | | X-25/100 | | 2x^2-12x-12= | | 37=29-2(x-1) | | 0.09xX=115.80 | | 8/50= | | w=8s+p | | -16+26=2(x+1) | | .75x+3=x+.5 | | 6/3x-5=3/2x | | 2(x-10)=-8 | | 0.09xX=83.07 | | (-4±√20)/2 |

Equations solver categories